357 Lipopolysaccharide induces a pro-inflammatory response in isolated ruminal epithelial cells. (7th December 2018) - Kent-Dennis, C; Penner, G
Abstract: Translocation of lipopolysaccharide (LPS) across the ruminal epithelium may occur as a result of acidosis, potentially triggering a local immune response. The objective of this study was to investigate whether LPS would stimulate a pro-inflammatory response in cultured ruminal epithelial cells (REC). Primary REC were isolated from ruminal papillae from the caudal blind sac of the rumen from 4-mo old bull calves. Cells were grown in culture until confluence. Cells were exposed to 0, 10, 000, 50, 000 or 200, 000 EU/mL LPS for either 6h (n=6) or 24h (n=8), after which cells were analyzed for viability (% dead) with propidium iodide by flow cytometry. Total RNA was extracted and expression was quantified for inflammation-related genes including: pro-inflammatory cytokines (TNFα; IL-1β; and CSF2), chemokines (CXCL2 and CXCL8), lipid mediators of inflammation (PTGS2 and LTA4H), a T-cell growth factor (IL-7) and an anti-inflammatory mediator (PPARγ). Gene expression was analyzed by real-time qPCR, normalized to the geometric mean of three stable housekeeping genes. Statistical analysis was performed using the MIXED procedure of SAS, with LPS concentration and time as fixed effects. Following exposure to LPS, the percent of dead cells did not differ. Exposure to LPS increased expression of IL-1β more than 170-fold ( P < 0.01) and increased expression of TNFα, CXCL2, CXCL8, IL-7, and CSF2 more than 2-fold ( P < 0.05), regardless of the concentration. An interaction was observed for IL-7 ( P = 0.02); expression was greater for LPS-exposed cells at 6h compared with 24h. TNFα, PTGS2 and LTA4H had greater expression at 24h. ( P < 0.05). There was no effect of LPS exposure on expression of PTGS2, LTA4H or PPARγ. The results of this experiment provide evidence that cultured REC are capable of inducing the production of pro-inflammatory molecules, suggesting a role in mediating an acute local response to LPS.